Personality Testing of Salespeople Working in Finance - Juhász, István (Public Finance Quarterly, 2023)
The main objective of my research was to explore whether there are differences between the personality of salespeople working in the finance and insurance sectors and that of ‘average’ Hungarian citizens. In answering this question, I relied on the 21 respective dimensions of the Short California Psychological Inventory. Accordingly, I examined a sample of 1,000 salespeople employed at banks, insurance companies, building societies, financial consultancy firms, factoring and leasing companies, savings associations and companies listed on the stock exchange. As a result of the application of a one-sample t-test in breakdown by gender, it could be concluded that, apart from the results obtained for Capacity for Status, Ego Strength, Good Impression and Communality for women included in the sample, and Capacity for Status and Psychological-Mindedness for men included in the sample, which do not show a statistically justifiable divergence from standard values, the rest of the values do show a significant divergence. Consequently, in the majority of the 21 personality dimensions, divergences can be noted between the test sample and the standard values. These findings should definitely be taken into account during human resource management, and particularly during employee selection, in the financial sector.